Donanemab in Early Alzheimer’s Disease - Mintun, Mark A; Lo, Albert C; Duggan Evans, Cynthia; Wessels, Alette M; Ardayfio, Paul A; Andersen, Scott W; Shcherbinin, Sergey; Sparks, JonDavid; Sims, John R; Brys, Miroslaw; Apostolova, Liana G; Salloway, Stephen P; et al. (The New England journal of medicine, 2021)
A phase 2 trial of donanemab, an antibody that targets amyloid deposited in the brain, showed a better composite score for cognition and for the ability to perform activities of daily living than placebo at 76 weeks in patients with early Alzheimer’s disease. Results for secondary outcomes were generally similar in the two trial groups.